2012
DOI: 10.4049/jimmunol.1200065
|View full text |Cite
|
Sign up to set email alerts
|

CD5-Dependent CK2 Activation Pathway Regulates Threshold for T Cell Anergy

Abstract: CD5 activates CK2, a serine/threonine kinase that constitutively associates with the CK2-binding domain at the end of its cytoplasmic tail. To determine the physiological significance of CD5-dependent CK2 activation in T-cells we generated a knock-in mouse that expresses a CD5 protein containing a microdeletion with selective inability to interact with CK2 (CD5ΔCK2BD). The levels of CD5 on developing and mature T-cell populations from CD5ΔCK2BD mice and CD5WT mice were similar. The thymus of CD5ΔCK2BD mice con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 45 publications
4
78
0
Order By: Relevance
“…2C). This method enumerates the proportion of cells progressing through the cell cycle during the short pulse labeling and therefore overcomes confounders such as cell death (37). We found that the proportion of EdU + cells was significantly reduced in TREX1 shRNA-transduced cells (p , 0.05, Fig.…”
Section: Silencing Of Trex1 Results In a Reduced Proliferation Of Endmentioning
confidence: 83%
“…2C). This method enumerates the proportion of cells progressing through the cell cycle during the short pulse labeling and therefore overcomes confounders such as cell death (37). We found that the proportion of EdU + cells was significantly reduced in TREX1 shRNA-transduced cells (p , 0.05, Fig.…”
Section: Silencing Of Trex1 Results In a Reduced Proliferation Of Endmentioning
confidence: 83%
“…MOG 35-55 -specific (MOGp) Th1 and Th17 cells were generated as described previously (23, 24). Briefly, splenocytes and draining lymph node cells were obtained from male C57Bl/6 mice 12 d post-immunization with 150 μg MOGp (CPC Scientific, San Jose, CA) in complete Freund's adjuvant.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the CD5 receptor has also been described to contribute to cell survival through association of its C-terminal cytoplasmic region with the serine/threonine kinase CK2 [47,48]. Thus, the CD5-dependent CK2 activation would deliver anti-apoptotic signals likely involved in homeostatic T-and B1a-cell survival and eventually resistance to activation-induced cell death (AICD) [49].…”
Section: Cd5: a Negative Modulator Of Immune Responsesmentioning
confidence: 99%
“…Furthermore, the CD5 receptor has also been described to contribute to cell survival through association of its C-terminal cytoplasmic region with the serine/threonine kinase CK2 [47,48]. Thus, the CD5-dependent CK2 activation would deliver anti-apoptotic signals likely involved in homeostatic T-and B1a-cell survival and eventually resistance to activation-induced cell death (AICD) [49].The inhibitory signaling ability of CD5 has been linked to its cytoplasmic tail and more specifically to tyrosines embedded in the proximal region of the membrane [50] or the pseudoimmunoreceptor tyrosine-based motif [51,52]. Such a negative immunomodulatory ability positions CD5 as a putative "immune checkpoint regulator" in a similar way to that reported for cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed cell death-1 (PD-1), among others, whose blockade has open up new pathways for cancer immunotherapy [53].…”
mentioning
confidence: 99%
See 1 more Smart Citation